Discursive Sovereignty: How China Constructs Hong Kong as an “Internal Affair” - Ka Hang Wong (Journal of Pragmatics Research, 2026)
This study examines the discursive construction of sovereignty in Hong Kong through a critical discourse analysis of political speeches, legal documents, and press releases spanning from the 1984 Sino-British negotiations to the post-2020 National Security Law era. The research aims to investigate how the totalitarian party-state in China legitimizes its authority over Hong Kong while simultaneously ignoring forms of British nationality held by Hongkongers, and how democratic states, particularly the United Kingdom, respond through visa and asylum pathways. Using a qualitative methodology grounded in Critical Discourse Analysis, the study traces the historical and ideological roots of the narrative of “internal affairs” as constructed through key state discourses and examines how these discourses intersect with concepts of self-determination, civic participation, and legal frameworks. The findings reveal that China employs a combination of hegemonic persuasion and institutional control to frame Hongkongers’ political aspirations as illegitimate, while international responses reflect broader tensions between democratic protection and authoritarian compliance. The research highlights the ongoing contestation of norms surrounding sovereignty, rights, and freedom, illustrating how Hong Kong has become a frontline in the global struggle between democratic and authoritarian discourses. The study concludes that understanding these dynamics provides insight into the mechanisms through which states assert power, control narratives, and shape transnational perceptions of legitimacy, with implications for both international relations and civic activism.